2005
DOI: 10.1103/physrevlett.94.147203
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Magnetic Phases in(Ga,Mn)AsEpilayers

Abstract: Two different ferromagnetic-paramagnetic transitions are detected in (Ga,Mn)As/GaAs(001) epilayers from ac susceptibility measurements: transition at a higher temperature results from (Ga,Mn)As cluster phases with [110] uniaxial anisotropy and that at a lower temperature is associated with a ferromagnetic (Ga,Mn)As matrix with 100 cubic anisotropy. A change in the magnetic easy axis from [100] to [110] with increasing temperature can be explained by the reduced contribution of 100 cubic anisotropy to the mag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
48
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 24 publications
11
48
0
Order By: Relevance
“…In the meantime, the BMPs isolated from the FM network behave like fragmented superparamagnetic ͑SPM͒ particles. This picture of the mixed FM and SPM is supported by Monte Carlo simulations 20,21 and recent experiments; 22,23 it also successfully explains the high-field resistivity behavior in InMnSb. 11 This two-phase model makes physical sense due to the inevitable inhomogeneous Mn distribution, which leads to the relatively hole-rich FM regions coexisting with the less hole-rich SPM regions.…”
mentioning
confidence: 48%
See 1 more Smart Citation
“…In the meantime, the BMPs isolated from the FM network behave like fragmented superparamagnetic ͑SPM͒ particles. This picture of the mixed FM and SPM is supported by Monte Carlo simulations 20,21 and recent experiments; 22,23 it also successfully explains the high-field resistivity behavior in InMnSb. 11 This two-phase model makes physical sense due to the inevitable inhomogeneous Mn distribution, which leads to the relatively hole-rich FM regions coexisting with the less hole-rich SPM regions.…”
mentioning
confidence: 48%
“…The size of BMPs is estimated to be about 6 nm at 50 K. A somewhat larger BMP size was reported earlier for T Ͻ T C . 23 Since the BMP size decreases rapidly above T C , we believe our result is still reasonable. For T Ͻ T C , the percolating FM phase starts to contribute to xx , which leads to a nonzero A c , as shown in Fig.…”
mentioning
confidence: 48%
“…[11] Thus, these bifurcations strongly support the presence of inhomogeneous magnetic phases in (Ga,Mn)As epilayers. [10,11,16,17,18,19] For our samples, since the single-domain model pre-sented by Wang et al [30] is not realistic, we hereafter discuss the cluster/matrix model in our recent reports: [10,11] (Ga,Mn)As epilayers that show two different 100 cubic anisotropy and [110] uniaxial anisotropy are composed of a matrix phase with relatively low hole concentration and highly-hole concentrated (Ga,Mn)As clusters embedded in the matrix. In this model, the distribution in p is likely due to the inhomogeneous distribution of Mn ions.…”
Section: Samples and Experimentsmentioning
confidence: 99%
“…[20] Also, the inhomogeneous distribution of Mn ions such as Mn Ga -Mn Ga and Mn Ga -Mn I -Mn Ga is proposed in theoretical studies [25,26] and direct observation using scanning tunneling microscopy. [27] Low-temperature growth of (Ga,Mn)As also suggests the presence of a cluster-like Mn distribution: recently, we have reported on a possible origin of complex in-plane magnetic anisotropy in (Ga,Mn)As on the basis of a cluster/matrix model, [28,29] where (Ga,Mn)As epilayers on GaAs(001) consist of ferromagnetic (Ga,Mn)As cluster-like regions with [110] uniaxial anisotropy and a ferromagnetic (Ga,Mn)As matrix with 100 cubic magnetocrystalline anisotropy. It was found that the Curie temperature of the clusters is higher than that of the matrix and the magnetic properties of the clusters dominate the magnetic anisotropy of (Ga,Mn)As with a high hole concentration.…”
Section: Samples and Experimentsmentioning
confidence: 99%